"Dope Syllabus": Student Impressions of an Infographic-style Visual Syllabus - Angel Kaur (Georgia Southern University, 2021)
Despite its importance in the classroom, there has been limited research into the functional design of the syllabus as a means to motivate students to read and use it. This mixed methods study investigates student impressions of a 4-page full-length infographic-style visual syllabus. Identically formatted infographic syllabi were used in three courses with different student populations—a freshman seminar, a 300-level elective liberal arts course, and a 400-level minor elective course. Students completed a short questionnaire to capture their immediate reactions to the syllabus, followed by a longer questionnaire at the end of the semester. Across class standing, students strongly preferred an infographic syllabus and described it as easy to use, memorable, organized, and engaging. Students reported reading the infographic syllabus more completely, feeling less anxious about the course and more comfortable with its requirements due to the syllabus style. Recommendations for creating an engaging infographic-style visual syllabus are shared.